A multiple case study on the level of awareness among homeowners of sustainability in practices and purchase of kitchen equipment and materials - Flores, Daniella S.; Gallardo, Mildred M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This study examined Filipino homeowners' level of awareness of sustainability through their practices and selection of materials and equipment within their kitchens. Data was collected from ten respondents who belong to the middle class and have owned and resided in their Quezon City home for at least five years. Interviews were used to gather information about the sustainable practices done within the kitchen, including food storage, preparation, and waste management, as well as their awareness of the concept of sustainability. Oculars were used to create an inventory of materials and equipment found in their kitchens, which were evaluated in terms of resource consumption, use, and maintenance. The theory of sustainability was used as the theoretical basis for the study, which weighs environmental, economic, and social impacts of lifestyles, practices, and consumption patterns upon both the environment, resources, and communities. Based on the findings of the study, respondents' awareness of sustainability was most evident in their practices rather than selection of materials and equipment, and respondents showed more recognition towards "green living" rather than "sustainability". Primary motivators for engaging in sustainable practices included saving money and maintaining the cleanliness of the environment to prevent diseases. Primary hindrances were cost and convenience. In materials and appliances, significant concerns were durability and energy-consumption. To conclude, the study found that an approach to sustainable design must anticipate beyond materials and equipment, to the practices, priorities, and goals of the users.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Kitchen utensils -- Philippines -- Quezon City; Kitchen appliances -- Philippines -- Quezon City; Sustainable design -- Philippines -- Quezon City; Sustainable living -- Philippines -- Quezon City; Interior decoration -- Philippines -- Quezon City